Analisis Pengaruh Aplikasi Facebook Sebagai Strategi Pemasaran dalam Menjangkau Konsemen di Era Ekonomi Digital - M. Saiful Rahman; Muhammad Rasyad Al Fajar; Taman Firdaus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the influence of Facebook as a marketing strategy in reaching consumers in the digital economy era. The quantitative research approach emphasizes that the problems studied are more general and have a wide area, as well as a complex level of variation. Practically, this finding confirms that Facebook is one of the social media that has a strong influence in the development of marketing strategies, both in terms of building brand awareness, increasing customer interaction, and expanding market reach. Companies or business actors who utilize Facebook optimally have a great opportunity to create marketing strategies that are more effective and responsive to market needs. This study provides an overview that the use of social media, especially Facebook, has an important role in supporting more effective marketing activities. The existence of Facebook not only functions as a communication platform, but also as a strategic tool that is able to reach consumers widely and quickly. With the right approach, social media can be an integral part of the planning and implementation of modern marketing strategies. This finding underlines the importance of digital transformation in the business world, as well as encouraging the integration of information technology in promotional activities to create sustainable competitive advantages.